Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1016/s0022-5347(01)64504-x
|View full text |Cite
|
Sign up to set email alerts
|

Vasoepididymostomy for Vasectomy Reversal: A Critical Assessment in the Era of Intracytoplasmic Sperm Injection

Abstract: Vasoepididymostomy is more successful and more cost-effective than microsurgical epididymal sperm aspiration and intracytoplasmic sperm injection for vasectomy reversal. It does not expose the women to complications in the treatment of a male problem and it is indicated for treatment of epididymal obstruction secondary to vasectomy. Microsurgical epididymal sperm aspiration and intracytoplasmic sperm injection should be reserved for cases not amenable to surgical reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 20 publications
4
75
2
4
Order By: Relevance
“…13,21,29,30,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Most experts in this field agree that the technical experience of the surgeons is one of the most important factors for the success of VE. We reported our clinical experience of microsurgical LIVE in a series of 72 men with azoospermia due to epididymal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,21,29,30,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Most experts in this field agree that the technical experience of the surgeons is one of the most important factors for the success of VE. We reported our clinical experience of microsurgical LIVE in a series of 72 men with azoospermia due to epididymal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that upfront assisted reproduction combined with surgical sperm retrieval is an expensive option. Cost analyses performed by various investigators have consistently demonstrated that for men who have obstructive azoospermia, surgical reconstruction remains a more cost-effective option compared to upfront assisted reproduction, [20][21][22][23][24][25][26] particularly if the couples have a low willingness to pay. 24 In the hands of experienced microsurgeons, patency rate of over 90% can be achieved with microsurgical VE.…”
Section: Alternative Management Optionsmentioning
confidence: 99%
“…22 Sperm aspiration and advanced reproductive techniques should not be the first option if reconstruction is possible and costeffective. 23 Anabolic steroid use is on the rise and it is necessary to specifically ask the patient if he is using any type of illicit anabolic steroid compound or prescribed testosterone pharmaceutical (reviewed elegantly by de Souza and Hallak 24 ). It is not just the athletes and body builders that are of concern as testosterone supplementation as treatment for several nebulous indications (under the umbrella of 'hypogonadism') is being dispensed to men of all ages.…”
Section: The Medical and Surgical History: What Clues Might It Reveal?mentioning
confidence: 99%
“…In addition, even the less successful VES procedure still results in a spontaneous pregnancy rate of 31-56%. Furthermore, the cost per delivery after microsurgery and after MESA/ICSI is much in favour of surgical treatment [13].…”
Section: Art or Surgery ?mentioning
confidence: 99%